9514 1404 393
Answer:
y = -(x+1)^2 +3
Step-by-step explanation:
Translating f(x) left by 1 unit replaces x with x+1.
Translating f(x) up by 3 units replaces f(x) with f(x)+3.
Reflecting f(x) over the x-axis replaces f(x) with -f(x).
__
When y = x^2 is reflected over the x-axis, it becomes ...
y = -x^2
When y = -x^2 is translated 1 unit left, it becomes ...
y = -(x +1)^2
When y = -(x+1)^2 is translated 3 units up, it becomes ...
y = -(x +1)^2 +3
Answer:
13 units
Step-by-step explanation:
Im doin this in class to so i got you
the equation would be d=(8-(-5))2-(-3-(-2))2
Next solve in the parenthesis 13 power of 2 +-1 power of 2
Then do the powers 169+1
d=170
Then you square 170 which is 13.03840481
That simplifies to 13
yayyyy
Means solve for y=mx+b form
so
expand/distribute
y-5=3x+3
add 5 to both sides
y=3x+8
What in the world is that